MEMBUDAYAKAN LITERASI PADA MASYARAKAT DI KELURAHAN GUNUNG BAHAGIA BALIKPAPAN SELATAN - Maryatin, Maryatin; Yuliani, Tutik (Jurnal Terapan Abdimas, 2019)
Abstract.  Literacy culture in Indonesia is a very interesting issue to discuss. Given the literacy culture in Indonesia is still low and not ingrained in the community. In the midst of the rise of popular culture, books have never been a top priority. Even the people more easily absorb the culture of speaking and listening, rather than reading then pouring it in written form. Counseling and training in literacy cultivation is a reading activity for the community so they can think creatively and be able to follow changes such as the use of new innovations, the application of technology, and a mindset that is development-oriented. The result is reading or listening activities both from storytelling and watching videos.Keywords : literacy, reading, writing Abstrak. Budaya literasi di Indonesia menjadi persoalan yang sangat menarik untuk diperbincangkan. Mengingat budaya literasi di Indonesia masih rendah dan belum mendarah daging di kalangan masyarakat. Di tengah melesatnya budaya populer, buku tidak pernah lagi menjadi prioritas utama. Bahkan masyarakat lebih mudah menyerap budaya berbicara dan mendengar, dari pada membaca kemudian menuangkannya dalam bentuk tulisan. Penyuluhan dan pelatihan budidaya literasi ini merupakan kegiatan membaca untuk masyarakat sehingga dapat berpikir kreatif dan mampu mengikuti perubahan seperti penggunaan inovasi baru, penerapan teknologi, dan pola pikir yang berorientasi pada pembangunan. Hasilnya berupa kegiatan membaca ataupun menyimak baik dari mendongeng maupun menonton video.Kata Kunci: literasi, membaca, menulis